Experimental Evaluation of Pathy Accuracy of Hydraulic Excavator Fixture - Płonecki, L. (Engineering Transactions, 1996)
The paper provided experimental evaluation of the accuracy of programmed operational motions of the fixture of a single-bucket hydraulic excavator which was regarded as an automated earth-mover. The methodology of experimental investigations carried out at a K-111 excavator fixture stand was discussed and the obtained results were presented.